Evaluation of Uncertainty in the Determination of Pesticide Residues in Tea using GC-ECD - Yohanes Susanto Ridwan; Andreas Andreas; Dyah Styarini; Retno Yusiasih (Jurnal Kimia Terapan Indonesia, 2017)
Key indicator of quality in test results is the uncertainty value, which could be evaluated using several common approach. Uncertainty evaluation in a-endosulfan and bifenthrin in Oolong tea, and cypermethrin in green tea using bottom-up approach showed that uncertainty component arising from GC-ECD instrument calibration, method performance i.e. repeatability and recovery were the main contributors to total uncertainty. Uncertainty component arising from weighing, dilution factor, stock standard solution, calibration solution, and moisture correction had no significant effect to total uncertainty, hence they could be neglected. Relative standard uncertainty obtained for all of pesticides residue were 18.23, 10.44, dan 14.98% for a-endosulfan, bifenthrin, and cypermethrin, respectively. Comparison with 2/3 CV Horwitz of 17.33, 10.62, and 12.44%  respectively for all pesticide residues indicated that the evaluation of uncertainties were realistic